On Argentocypris sara gen. nov., sp. nov. (Ostracoda) from the Patagonian wetlands of Argentina - Diaz, Analia Roxana (2014)
We describe Argentocypris sara, a new genus and species from a Patagonian lake in the province of Neuquén, Argentina. The genus and species clearly belong to the tribe Eucypridini, and as such have a rather isolated biogeographical position in South America. The genus can be distinguished from other Eucypridini based on both valve (large external Porenwarzen, anterior selvage and posterior inner list on RV) and soft part features (cylindrical shape of second distal segment of Mx1-palp, length ratio setae d1 = c 3 × d2 on T2, curved attachment of caudal ramus). A study of the literature reveals that several other nominal species can be transferred to this genus. Nevertheless, at least two of these species (A. virgata n. comb. and A. labyrinthica n. comb.) are based on juvenile fossil specimens only and their identity is uncertain. Two other species (A. fontana n. comb. and A. sarsi n. comb.) are based on adult morphology.